Copyright Dispute Resolution in the Technology Industry: Case Study of PT Application Karya Anak Bangsa and Nadiem Makarim - Stella, Helen (CV. Rayyan Dwi Bharata, 2024)
Copyright violations in the digital technology industry in Indonesia have a significant impact on the development of innovation and company growth. Law no. 28 of 2014 concerning Copyright functions as a legal framework to protect copyrighted works in the technology sector, but copyright lawsuits often pose challenges for companies, especially startups, in innovating. Excessive or misused lawsuits can create barriers to competition and slow the pace of technological innovation. On the other hand, copyright protection remains important to maintain justice for technology creators. Dispute resolution through litigation and non-litigation channels, including mediation and arbitration, provides alternatives for the parties involved. The litigation route, although offering legal certainty, is often considered slow and expensive. In contrast, non-litigation settlement is more flexible, fast and economical. Both of these mechanisms are regulated by applicable law in Indonesia and allow parties to choose the resolution that best suits their needs. It is important for technology companies to consider effective dispute resolution strategies so that innovation can continue to develop without excessive obstacles.